Assessment of heat exchanger degradation in a Boeing 737-800 environmental control system - Jennions, Ian; Ali, Fakhre (American Society of Mechanical Engineers (ASME), 2021)
There are a number of systems on an aircraft working together, in harmony, to produce safe and trouble free flight. The Environmental Control System (ECS) is one of these systems, and its failure is a major contributor to unscheduled maintenance, particularly in older aircraft. The ECS is composed of several complex sub-systems and components, but at its heart is the passenger air conditioner (PACK). The PACK is prone to degradation, which can lead to the functional failure of the ECS. Often its degradation is masked by the overall ECS control system and this can, ultimately, result in the ECS shutting down and extensive maintenance being required. There are a number of critical fault modes associated with the PACK, and in this paper those modes associated with the primary and secondary heat exchangers are explored. A robust ECS simulation framework called SESAC (Simscape ECS Simulation under All Conditions) has previously been implemented, calibrated, and tested, against data from healthy systems. Here the simulations are extended to cover degraded components in a representative Boeing 737-800 aircraft PACK model. Fault modes such as blockage and fouling are assessed for the primary and secondary heat exchangers of the PACK. Simulation results, in terms of temperature, pressure and mass flow at various degradation severities, are presented and discussed. The results highlight the interdependency between the PACK components, and the strong association between the primary and secondary heat exchanger performance.
Keywords: Thermal Systems; Heat Exchangers; Fouling; Energy Systems; Aerospace Heat Transfer